2006
DOI: 10.1111/j.1365-2958.2006.05510.x
|View full text |Cite
|
Sign up to set email alerts
|

The Saccharomyces cerevisiae Crs5 Metallothionein metal‐binding abilities and its role in the response to zinc overload

Abstract: Crs5 is a Saccharomyces cerevisiae Metallothionein (MT), non-homologous to the paradigmatic Cu-thionein Cup1. Although considered a secondary copper-resistance agent, we show here that it determines survival under zinc overload in a CUP1-null background. Its overexpression prevents the deleterious effects exhibited by CUP1-CRS5-null cells when exposed to combined Zn/Cu, as it does the mouse MT1 Zn-thionein, but not Cup1. The detailed characterization of Crs5 in vivo and in vitro Zn(II)-, Cd(II)- and Cu(I)-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
82
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 35 publications
5
82
0
3
Order By: Relevance
“…This is in contrast with the situation in S. pombe, which encodes the Zym1 Zn-thionein (Borrelly et al, 2002). In a recent characterization of the metal binding properties of Crs5, an unexpected toxic effect of the combination of zinc and copper was reported, which puts forward a connection between the zinc-and copper-handling pathways in this organism (Pagani et al, 2007).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…This is in contrast with the situation in S. pombe, which encodes the Zym1 Zn-thionein (Borrelly et al, 2002). In a recent characterization of the metal binding properties of Crs5, an unexpected toxic effect of the combination of zinc and copper was reported, which puts forward a connection between the zinc-and copper-handling pathways in this organism (Pagani et al, 2007).…”
Section: Introductionmentioning
confidence: 79%
“…MT can be classified, on the basis of their in vivo metal binding preferences and sequence features, as Zn-thioneins and Cu-thioneins (Valls et al, 2001). S. cerevisiae encodes the paradigmatic Cup1 Cu-thionein (Winge et al, 1998) and the dual Zn-Cu-thionein Crs5 (Pagani et al, 2007), but no specific zinc immobilizing protein is present in this organism. This is in contrast with the situation in S. pombe, which encodes the Zym1 Zn-thionein (Borrelly et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Pagani et al (41), however, reported the involvement of the Crs5 Cu-metallothionein of S. cerevisiae in Zn detoxification. Tucker et al (47) described an MT-like protein in Magnaporthe grisea which showed a very high affinity to Zn.…”
Section: Discussionmentioning
confidence: 99%
“…The first one is encoded by the CUP1 locus and is induced by Cu and Ag but not by other heavy metals (8,40). The second one, Crs5, is regulated by Cu, Zn, and oxidative stress (14,41). An MT has been identified for Agaricus bisporus (37), Gigaspora margarita (29), Neurospora crassa (38), Pyrenopeziza brassicae (44), Podospora anserina (2), and P. involutus (6).…”
mentioning
confidence: 99%
“…preparations that result from the recombinant synthesis of MT2 and MT3 in Cusupplemented E. coli cultures grown under regular aeration, [20] which is the closest approximation to mammalian cell conditions. They yielded a mixture of Zn 1 Cu 10 -and Zn 2 Cu 10 -as major species for MT2 [17] and a mixture of Zn 4 Cu 6-and Cu 10 -complexes for MT3 [18] , which from now on and for the sake of simplicity we shall refer to as the Cu-MT2 and Cu-MT3 complexes.…”
mentioning
confidence: 99%